A Reevaluation of the Effects of State and ACA Dependent Coverage Mandates on Health Insurance Coverage. (9th May 2020) - Barkowski, Scott; McLaughlin, Joanne Song; Ray, Alex
Abstract: We study state and federal health insurance coverage mandates for young adults. Despite consistent findings that the Affordable Care Act's (ACA) federal mandate was effective, research has disagreed on whether preexisting, state‐level mandates were successful in increasing coverage. We reconsider the issue with a new analytical perspective and newly available accurate data on state mandates. We show that the impact of the state mandates was substantive and concentrated among young adults between ages 19 and 23. Our estimates indicate that dependent coverage rose by 3.9 percentage points and overall coverage rose by 3.3 percentage points. Crowd‐out of coverage through young adults' own jobs was negligible. For those above 23, we find little evidence of changes in coverage. We incorporate these insights into analysis of the ACA's mandate, showing its effects were focused among those who were not eligible for state mandates, or were eligible but older than 23. Our results suggest that eligibility restrictions played important roles in limiting the scope of the state mandates, but they can be practical and effective tools for policymakers looking to ensure or expand coverage for young adults in the face of uncertainty about the ACA.